Eficacia del carbón activo de origen mineral y vegetal como agente blanqueador, sobre dientes permanentes no vitales (2020)
The present investigation allows to know the effectiveness of the active coal of mineral and vegetable origin as a bleaching agent in non-vital teeth, in this way to know its effectiveness as an alternative of teeth whitening. Through a longitudinal study, the variation of the tone was determined in two pairs of teeth of the previous sector submerged in artificial saliva, after being brushed with activated charcoal of mineral and vegetable origin for 60 (sixty) days, performing chromatization tests with A stereoscopic microscope. with 30-day intervals, technologies provided in conjunction with the SENA (National Learning Service). The main findings of this research, allow to show rechromia and dyschromia, that is, change of tone of the vestibular surfaces of the teeth. When comparing the results of samples 1 and 3 submitted to activated charcoal of vegetable origin, a whitening of the surface of the tooth was evident, while samples 3 and 4 brushed with mineral activated carbon, evidence in the 4th sample a tone more darkness. The relevance of the aforementioned results, provides scientific evidence on these agents, highlighting that one of its characteristics is the abrasion of dental enamel exposing the dentine that under prolonged and unregulated use is translucent generating an impact on the tone contrary to the expected.